Genetic Considerations in Human Sex‐Mate Selection: Partners Share Human Leukocyte Antigen but not Short‐Tandem‐Repeat Identity Markers. (3rd March 2014) - Israeli, Moshe; Kristt, Don; Nardi, Yuval; Klein, Tirza
<x xml:space="preserve">Abstract</x> Problem Previous studies support a role for MHC on mating preference, yet it remains unsettled as to whether mating occurs preferentially between individuals sharing human leukocyte antigen (HLA) determinants or not. Investigating sex‐mate preferences in the contemporary Israeli population is of further curiosity being a population with distinct genetic characteristics, where multifaceted cultural considerations influence mate selection. Method of study Pairs of male–female sex partners were evaluated in three groups. Two groups represented unmarried (n = 1002) or married (n = 308) couples and a control group of fictitious male–female couples. HLA and short‐tandem‐repeat (STR) genetic identification markers were assessed for the frequency of shared antigens and alleles. Results Human leukocyte antigen results showed that Class I and/ or Class II single antigen as well as double antigen sharing was more common in sex partners than in control group couples (P < 0.001). Married versus unmarried pairs were not distinguishable. In contrast, STR‐DNA markers failed to differentiate between sex‐mates and controls (P = 0.78). Conclusion Sex partnerships shared HLA determinants more frequently than randomly constituted male–female pairs. The observed phenomenon does not reflect a syngenetic background between sex‐mates as STR markers were not selectively shared. Thus, sex‐mate selection in man may contravene the evolutionary pressure for genetic diversity in regard to HLA.